Ex-ante margin squeeze tests in the telecommunications industry: What is a reasonable efficient operator? (Revised: December 20, 2012) - Germain Gaudiny; Claudia Saavedra Valenzuela (International Telecommunications Society (ITS), 2012)
We study the implementation of reasonably efficient operator margin squeeze tests by National Regulatory Authorities in European telecommunications markets. We provide a theoretical framework in which we show how regulatory authorities deal with the asymmetries between the entrants and the incumbent by adjusting the equally efficient operator margin squeeze test used in competition policy. Using this framework, we build a benchmark of implementation choices by inspecting authorities' guidelines, market analyses and decisions. We find that some implementation choices are very similar across the authorities' decisions, whereas some others are dealt with quite heterogeneously.
Additional information: Revised Version: December 20, 2012
Keywords: L51; L96; 330; Margin squeeze; Imputation test; Regulation; Telecommunications